Guidance Group Based on Islamic Teachings with Simulation Game Techniques to Improve Interpersonal Communication - Listiyani, Nurul; Wibowo, Mungin Eddy; Sutoyo, Anwar (Jurnal Bimbingan Konseling, 2019)
The purpose of this study was to determine the effectiveness of group guidance based on Islamic teachings with simulation game techniques in improving student interpersonal communication. The experimental research method uses the design of One Pre-test – Post-test Design with a purposive sampling technique to determine the research subjects of VII grade Madrasah Tsanawiyah as many as 10 people who have low interpersonal communication. Validation of this experimental study with guidance and counseling experts, and MTs level counselors in Kudus Regency. The results of this study indicate that interpersonal communication of students before being given group guidance based on Islamic teaching simulation techniques, the average interpersonal communication amounted to 107.71 (SD = 8.51), then increase after group guidance based on Islamic teaching amounted to 136.86 (SD = 9.02). The paired sample t-test results showed group guidance based on Islamic teaching effective simulation techniques to improve interpersonal communication of MTs students (t(9) = 14.93, p < 0.01). This study confirms that group guidance based on Islamic teaching with simulation techniques can be applied to improve student interpersonal communication.